1985
DOI: 10.1111/j.1365-2125.1985.tb02794.x
|View full text |Cite
|
Sign up to set email alerts
|

A dose‐response study of HOE 498, a new non‐sulphydryl converting enzyme inhibitor, on blood pressure, pulse rate and the renin‐ angiotensin‐aldosterone system in normal man.

Abstract: 1 The effect of different oral doses of HOE 498, a new non-sulphydryl containing converting enzyme inhibitor, was investigated in a double-blind, placebo-controlled study in normotensive volunteers. 2 Dose-related reductions in serum converting enzyme activity, plasma angiotensin II and aldosterone were seen, greater at 4 h than at 12 h after drug ingestion. Converse doserelated increases in blood angiotensin I and plasma active renin concentration occurred. 3 Falls of angiotensin II were as great with 20 mg a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…The high-performance liquid chromatography separation used for the Ang II measurements excludes angiotensin fragments that would cross-react with the assay antiserum. The results obtained with this very accurate method nevertheless confirm previous observations made with enalapril, lisinopril, 20 and ramipril 21 where only immunoreactive Ang II was quantitated. The time course of plasma and urinary aldosterone was similar to that of plasma Ang II.…”
Section: Juilkrat Et Al Plasma Ang II During Ace Inhibition 571supporting
confidence: 87%
See 1 more Smart Citation
“…The high-performance liquid chromatography separation used for the Ang II measurements excludes angiotensin fragments that would cross-react with the assay antiserum. The results obtained with this very accurate method nevertheless confirm previous observations made with enalapril, lisinopril, 20 and ramipril 21 where only immunoreactive Ang II was quantitated. The time course of plasma and urinary aldosterone was similar to that of plasma Ang II.…”
Section: Juilkrat Et Al Plasma Ang II During Ace Inhibition 571supporting
confidence: 87%
“…Clearly, Ang II is the pivotal parameter in the closed loop, and the system works to compensate any interference by adjusting renin secretion to restore as rapidly and completely as possible normal Ang II levels. Although they did not perform such calculations, Manhem et al 21 observed that the administration to normal volunteers of ramipril at doses varying from 5 to 50 mg did not influence plasma Ang II 24 hours after drug intake, whereas a dose-dependent rise in plasma renin and Ang I was described. A dose-dependent increase in Ang I levels and plasma active renin was also found during a 10-day administration of trandolapril to normal volunteers: on day 10, plasma immunoreactive Ang II was equally reduced over the 16-fold dose range of drug.…”
Section: Juilkrat Et Al Plasma Ang II During Ace Inhibition 571mentioning
confidence: 99%
“…data (Bussien et al, 1985;Witte et al, 1984;Manhem et al, 1985) and confirm that ACE was significantly inhibited.…”
Section: Plasma Ramiprilat Concentrationsmentioning
confidence: 80%
“…The parent drug, ramipril, which is a dicarboxylic acid monoethyl ester, must be converted in the liver to its active metabolite, ramiprilat. The extent of ramipril absorption and hydrolysis to ramiprilat appears to be similar over the dose range 5 to 50mg as the maximal plasma concentration (Cmax) of ramiprilat was linearly related to the dose of ramipril over this range (Manhem et al 1985).…”
Section: Absorption and Bioavailabilitymentioning
confidence: 94%